Equipamento para verificação de múltiplos compartimentos em silos de transporte de ração - Wolfardt, Gustavo Rocco (2024)
Due to the growth of livestock farming in Brazil, the importance of animal feed transportation is increasing. It is necessary to comply with safety regulations during product manufacturing, both during transport and unloading processes. To simplify and optimize fieldwork while minimizing worker risk, a project was developed using cameras, a Raspberry Pi-based computational system with WiFi communication, and a user interface. This system allows truck drivers to photograph the inside of the silo to verify the presence of feed. Operating at high speed, with approximately 2 seconds between the command to take a photo and its retrieval on the driver’s cell phone, the system provides rapid, high-quality images in both well-lit and dark environments. This device reduces the need for workers to climb onto the truck silo, provides proof of compartment discharge, and facilitates company reporting. With easy installation and simplified connections, the user-friendly interface indicates connection status and potential errors. Overall, this system enhances driver safety, streamlines the feed delivery process for breeders, and allows generated images to be used for reports and delivery confirmations.